Hospital‐based community psychiatric service for patients with schizophrenia in Kuala Lumpur: A 1‐year follow‐up study of re‐hospitalization. (17th April 2013) - Dahlan, Rahima; Midin, Marhani; Sidi, Hatta; Maniam, T.
Abstract: Introduction: Hospital‐based community psychiatric service (HCPS) is a developing intervention in Malaysia targeted for patients with severe mental illnesses (SMIs). Its effectiveness had not been systematically measured. This study aimed to assess the outcome of HCPS with respect to re‐hospitalization and factors associated with low re‐hospitalization among patients with schizophrenia in the metropolitan city of Kuala Lumpur. Methods: A naturalistic and retrospective cohort study was conducted using within‐subject pre‐post design on 155 patients with schizophrenia who received HCPS in Hospital Kuala Lumpur (HKL). The selection was made by simple random sampling. The hospital admission profiles were obtained from clinical records. The socio‐demographic and relevant clinical data were also assessed through clinical interviews. Results: One hundred and forty (90%) of 155 respondents had low rate of hospital admission with significant reduction of being hospitalized within 1 year after receiving HCPS (p < 0.001). Having good social support was significantly associated with lower rate of rehospitalization (p = 0.001). Discussion: The study revealed the effectiveness of HCPS in terms of reducing rates of hospital admission among patients with schizophrenia in Malaysia. The finding may be used as an evidence to develop the service further in other hospitals. However, the finding needs to be replicated through studies with better design involving more psychiatric centres.